Droplet transfer behavior and weld formation of gas metal arc welding for high nitrogen austenitic stainless steel. (May 2021) - Dongqing, Yang; Hanying, Xiong; Yong, Huang; Dejun, Yan; Dong, Li; Yong, Peng; Kehong, Wang
Abstract: High nitrogen austenitic stainless steel (HNASS) wire with 0.78 wt.% nitrogen content was used for gas metal arc welding (GMAW) test. The characteristics of droplet transfer and weld formation in different welding parameters were investigated. There were three typical metal transfer modes in GMAW of HNASS, namely in terms of stable short circuit transfer, unstable short circuit transfer and spray transfer. With wire feed speed (WFS) of 3 m/min∼8 m/min and moderate arc voltage, the droplet transfer was stable short-circuiting transition mode. The transfer period and waveform of electrical parameters were regular and the weld formation was satisfactory with few spatters. With the increasing of arc voltage or WFS, the droplet grew up to abnormal large size due to the expansion of supersaturated nitrogen. The electric parameters were more disordered and the metal transfer became unstable with spatter. When wire feed speed was over 10 m/min with high arc voltage, the droplet transfer became spray transfer accompanied by numerous welding fumes. The weld formation of HNASS for unstable short circuit and spray transfer mode was inferior with serious spatters.